2020
DOI: 10.31274/jctp.9571
|View full text |Cite
|
Sign up to set email alerts
|

Attributes Associated with Postdoctoral Fellows and Views of Immigration: A Preliminary Analysis Using the General Social Survey

Abstract: While research on supporting undocumented immigrants and undocumented students within higher education has examined the opinions of students, faculty, and staff, there is a gap in the literature when it comes to postdoctoral fellows. This study used data from the 2014 General Social Survey (Smith et al., 2018) to examine whether respondents' attributes, including holding a possible postdoctoral position, predicted views of "illegal" immigration, and whether immigrants should have the same education as American… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…This study builds on previous literature regarding attributes and experiences associated with greater support for undocumented students' higher education pursuits. Specifically, prior research has shown that being of a minoritized race/ethnicity, being a woman, and being a non-native English speaker (Garibay et al, 2016), as well as having higher levels of education (Berg, 2009;Kunovich, 2013) and being a non-U.S. Citizen (Jach & Gloeckner, 2020) are associated with greater support of undocumented students' pursuit of higher education and immigrant education, and this study examined how individuals who are White U.S. citizens make sense of their attitudes to support undocumented students' pursuit of higher education.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study builds on previous literature regarding attributes and experiences associated with greater support for undocumented students' higher education pursuits. Specifically, prior research has shown that being of a minoritized race/ethnicity, being a woman, and being a non-native English speaker (Garibay et al, 2016), as well as having higher levels of education (Berg, 2009;Kunovich, 2013) and being a non-U.S. Citizen (Jach & Gloeckner, 2020) are associated with greater support of undocumented students' pursuit of higher education and immigrant education, and this study examined how individuals who are White U.S. citizens make sense of their attitudes to support undocumented students' pursuit of higher education.…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels of education have also been associated with more supportive views toward immigrants (Berg, 2009;Kunovich, 2013). Identifying as a non-U.S. citizen has also been found to be related to greater support for immigrant education (Jach & Gloeckner, 2020). While these factors certainly do not describe all postdocs, there are several connections between factors associated with greater support of undocumented students as well as immigrants and the demographics of postdocs.…”
Section: Attributes Associated With Attitudes Toward Undocumented Stu...mentioning
confidence: 99%
See 1 more Smart Citation